A Study on M/M/3 Queuing Model on Waiting time Reduction in a Hospital: Optimizing patient allocation and reducing waiting times (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This paper contains the analysis of queuing system in hospital management is the mathematicalapproach to the analysis of waiting lines in any setting where arrival. The goal of this paper explains theproblem in their urgency of medical cases with respect to allocation problem of the patients and utilizationthe waiting line. We assume first service times first come first served queue discipline.